Factors predicting hospital readmission of palliative care patients at Lamphun Hospital - Promarat, Chortip (Journal of Nakornping Hospital, 2025)
Introduction: Readmission of some palliative care patients may affect their families and the healthcare system. Objective: This study aimed to study the factors predicting hospital readmission within 30 days among patients receiving palliative care to identify the risk factors for readmission and to further develop the quality of care. Methods: A retrospective cohort study of all palliative care patients in the inpatient department of Lamphun Hospital between October 2022 and September 2024. Baseline and clinical data were analyzed using descriptive statistics, and associated with hospital readmission were analyzed using logistic regression. Results: A total the 529 palliative care patients receiving hospital care, 96 patients were readmitted within 30 days. 51.42% were female, 65.97% were over 65 years old, and 59.92 % were not cancer. Factors predicting hospital readmission within 30 days were living at nursing home (Adj.OR 36.99,95%CI 8.95- 152.98, p<0.001), moderate to high performance of patients at PPS 40-60 (AdjOR10.56,95%CI 6.03- 18.48, p<0.001) PPS 70-100 (Adj.OR 13.24,95%CI 4. 43- 39.59, p<0.001) and the lack of assessment and care planning by the palliative care team before discharge (Adj.OR 3.69,95%CI 1.88- 7.24, p<0.001) respectively. The main reason of readmission to the hospital within 30 days causes of primary palliative care disease 65.62%. Most of the palliative care patients who were readmitted to the hospital requested to die at home 47.91%. Conclusion: Factors predicting with hospital readmission within 30 days among palliative care patients included living in a nursing home, moderate to high performance status of patients, and lack of assessment and care planning by the palliative care team before discharge, respectively.